2002
DOI: 10.1046/j.1365-2958.2002.02863.x
|View full text |Cite
|
Sign up to set email alerts
|

The luxS gene is involved in cell–cell signalling for toxin production in Clostridium perfringens

Abstract: Summary A Gram‐positive anaerobic pathogen, Clostridium perfringens, causes clostridial myonecrosis or gas gangrene in humans by producing numerous extracellular toxins and enzymes that act in concert to degrade host tissues. C. perfringens possesses a homologue of the luxS gene that is reported to be responsible for the production of autoinducer 2 (AI‐2), which participates in quorum sensing in bacteria. The luxS mutant was constructed using C. perfringens strain 13, and the role of the luxS gene in tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 31 publications
6
115
1
Order By: Relevance
“…When the concentration of the autoinducers reaches a threshold, an alteration of gene expression is induced, allowing the bacteria to adopt behaviors that are only productive when the bacteria are working together as a group [3,4]. Among many different mechanisms for QS by bacteria, one is shared by both gram-negative and gram-positive bacteria, involving the production of autoinducer 2 (AI-2) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of the autoinducers reaches a threshold, an alteration of gene expression is induced, allowing the bacteria to adopt behaviors that are only productive when the bacteria are working together as a group [3,4]. Among many different mechanisms for QS by bacteria, one is shared by both gram-negative and gram-positive bacteria, involving the production of autoinducer 2 (AI-2) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, AI-2 production was verified in a large number of species and the AI-2 QS system was recognized to be involved in the regulation of a range of functions in diverse bacteria [6,7,10,[12][13][14]. In contrast to other autoinducers that are specific for a narrow range of organisms, the widely conserved AI-2 has been hypothesized to be a universal language for interspecies communication [6,9,10,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of many bacterial species, notably Escherichia coli, Salmonella enterica serovar Typhimurium, Shigella flexneri, Proteus mirabilis, Vibrio cholerae, Vibrio vulnificus, Campylobacter jejuni, Porphyromonas gingivalis, Bacillus subtilis, Streptococcus pyogenes, Streptococcus mutans, Clostridium perfringens and Clostridium difficile, include luxS homologues. In several of these, luxS-related AI-2 signals are involved in bacterial characteristics such as biofilm formation (Balestrino et al, 2005;Blehert et al, 2003;Fong et al, 2001;Wen & Burne 2004), flagella and motility (Jeon et al, 2003;Schneider et al, 2002;Stroeher et al, 2003), type III secretion systems (Sperandio et al, 1999), toxin production (Ohtani et al, 2002) and virulence (Lyon et al, 2001; Parsonnet et al, 1991;Stroeher et al, 2003).Helicobacter pylori has been identified as the aetiological agent of chronic active gastritis, peptic ulcer disease (Blaser, 1992;Graham, 1989), gastric adenocarcinoma (Parsonnet et al, 1991) and mucosal-associated lymphoid tissue (MALT) lymphoma (Wotherspoon et al, 1993). H. pylori has flagellar motility and is able to move through the Matsumoto et al, 1997;Yokota et al, 1991).…”
mentioning
confidence: 99%
“…Pathogenic bacteria commonly sense environmental changes using two component regulatory systems and quorum sensing systems in order to optimize their production of virulence factors such as toxins. Earlier studies [12][13][14] had shown that, for C. perfringens type A strain 13 growing in bacterial media, expression of α-toxin and PFO is regulated by both the VirS/ VirR two component regulatory system and the LuxS quorum sensing system. Therefore, we investigated 11 whether those systems might also be involved in the host cell-induced upregulation of toxin production by type C isolates.…”
Section: Introductionmentioning
confidence: 99%